Constructing a Coincident Economic Indicator for India: How Well Does It Track Gross Domestic Product? - SOUMYA BHADURY; SAURABH GHOSH; PANKAJ KUMAR (Asian Development Review, 2021)
In India, the first official estimate of quarterly gross domestic product (GDP) is released approximately 7–8 weeks after the end of the reference quarter. To provide an early estimate of current quarter GDP growth, we construct Coincident Economic Indicators for India (CEIIs) using a sequentially expanding list of 6, 9, and 12 high-frequency indicators. These indicators represent various sectors, display high contemporaneous correlation with GDP, and track GDP turning points well. CEII-6 includes domestic economic activity indicators, while CEII-9 incorporates indicators of trade and services and CEII-12 adds financial indicators in the model. We include a financial block in CEII-12 to reflect the growing influence of the financial sector on economic activity. CEIIs are estimated using a dynamic factor model which extracts a common trend underlying the high-frequency indicators. The extracted trend provides a real-time assessment of the state of the economy and helps identify sectors contributing to economic fluctuations. Furthermore, GDP nowcasts using CEIIs show considerable gains in both in-sample and out-of-sample accuracy. In particular, we observe that our GDP growth nowcast closely tracks the recent slowdown in the Indian economy.